Overcoming claustrophobia in cardiovascular magnetic resonance with medical hypnosis. (13th July 2021) - Pavon, A; Chautems, C; Odin, Y; Arangalage, D; Rutz, T; Hugelshofer, S; Monney, P; Schwitter, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: the role of Cardiovascular Magnetic Resonance has gained the more and more importance in the field of cardiovascular disease. Claustrophobia remains a frequent cause of failure to complete a CMR. It is estimated that 2 million scans worldwide cannot be performed annually either due to premature termination or refusal of the patient to be scanned due to claustrophobia. In this setting, medical hypnosis may prove useful to overcome this main limitation. Methods: we propose an observational study of consecutive patients referred to CMR and known for severe claustrophobia. Patients were proposed to undergo CMR examination with the help of medical hypnosis according to Milton H. Erickson's method or with administration of mild sedation (lorazepam 2.5 mg). Results: 20 severe claustrophobic patients were considered in the study. 1 patient was excluded due to psychiatric condition, 1 patient undergo to general anesthesia, 5 patients refused the examination. Among the 13 patients, 10 underwent medical hypnosis while 3 patients accepted to undergo to CMR examination with the administration of lorazepam 2.5 mg. All patients treated with medical hypnosis were able to complete the examination with a great tolerance and no sign of stress or anxiety were reported. CMR protocol was performed according to clinical request and was not different form non-claustrophobic patients. None of the patients treated with lorazepam 2.5mg was able to complete the exam. Conclusion: we prove medical hypnosis to be safe and effective in controlling patients' anxiety, allowing optimal diagnostic imaging quality without the need to adapt the examination. Further studies in larger populations are needed to confirm our results.